Respon Petani Terhadap Perkembangan Teknologi dan Perubahan Iklim: Studi Kasus Subak di Desa Gadungan, Tabanan, Bali - Sukartini, Ni Made; Solihin, Achmad (Jurnal Ekonomi Kuantitatif Terapan; 2013: Vol. 6, No. 2, Agustus 2013 (pp. 71-143))
Agricultural sector is one of the economy’s sector well known for it slowly adapt the tehcnological progress as well as the most vulnerable sector affected by climate change. This study will analyze how technological adaptation by the farmers can improve the productivity of rice output, and investigate how social capital in the community can minimalize the downside effect of the climate change. We run the data with linear and logistic regression. Our study find that among several variables, only the plot size matters in determine the harvesting output volume. Technological adoption and set of farmers’ individual characteristics are not statistically significant influence the output variation. Our study infer this insignificant relation between technological adoption and farmers’ characteristic due to non linearity in relation between these variables. Based on our study finding, we would suggest the policy maker in Bali’s agricultural sector to minimize the possibility of land conversion from ricefield to other business activity of real estate, for example.
Keywords: technology adoption , climate change , agriculture , Subak